Stability of vacancy-oxygen complexes in bulk nickel: Atomistic and ab initio calculations - Zenia, H.; Lounis, K.; Megchiche, E.H.; Mijoule, C. (Computational materials science, 2016)
The optimized positions of oxygen atoms (blue) inside the cavity made by a single vacancy in nickel, obtained using the atomistic ReaxFF potential. The Ni atoms forming the cavity walls are depicted using a color scale reflecting their charges. [Display omitted] This work is concerned with the interactions of multiple oxygen atoms with vacancy clusters Vm of size m in bulk nickel. The calculations were carried out using molecular statics, employing a reactive potential developed recently for the NiO system containing vacancies. In particular, segregation of oxygen inside a mono- and a divacancy are considered for the first time, to complete earlier work on the subject. Overall, we find strong attractive interactions between the oxygen atoms and the vacancy clusters. We argue that this leads to increasing dramatically the solubility of oxygen in nickel. Regarding the complexes VmO1, the results indicate that atomic oxygen inside the vacancy clusters is more stable than at the conventional interstitial sites of the perfect Ni system. This stability is further enhanced as the size of the cavity increases. We have found that a monovacancy (V1) and a divacancy (V2) can trap up to 14 and 22 oxygen atoms, respectively. We have also carried out ab initio calculations, for the purposes of both comparison and validation of the potential used in the current work. We find a very good qualitative agreement between the ab initio results and the predictions obtained from the reactive potential. Both agree well with the experimentally observed facts establishing the influence of point defects on the oxidation processes observed in nickel and its alloys.